The Importance of Non Disclosure Agreement (Nda) As a Form of Trade Secret Protection in Foreign Higher Education Consultants in Indonesia - Arifardhani, Yoyo (Journal of Law, Politic and Humanities, 2025)
The development of the overseas higher education consulting industry in Indonesia has created a need for effective trade secret protection. This study aims to analyze the effectiveness of Non-Disclosure Agreements (NDA) as an instrument for protecting trade secrets, identify the challenges of their implementation, and formulate strategies to optimize compliance while maintaining employee career mobility. Using normative legal research methods with statutory, conceptual, and case approaches, this study analyzes primary, secondary, and tertiary legal materials related to the implementation of NDAs in the industry. The results show that the effectiveness of NDAs is highly dependent on the clarity of the clause formulation and the monitoring mechanisms applied. The main challenges include the difficulty of defining the boundaries of confidential information, the complexity of proving violations, and the limitations of post-employee monitoring mechanisms. Optimal strategies include the development of a structured knowledge management system, periodic training programs, and incentive mechanisms to encourage compliance. This study recommends the development of a standardized NDA template, strengthening monitoring mechanisms, and continuing education programs to improve the effectiveness of trade secret protection in the overseas higher education consulting industry in Indonesia